2020
DOI: 10.1002/lary.28780
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of Depression Screening for Otolaryngology–Head and Neck Surgery Residents

Abstract: Objectives This study aims to determine the cost‐effectiveness of screening and treating otolaryngology–head and neck surgery residents for depression. Methods A Markov model was built using TreeAgePro, version 2019 (TreeAge Software Inc.; Williamstown, MA) to assess the cost‐effectiveness of five potential treatment algorithms: 1) treat all residents with psychotherapy, 2) screen and treat depressed residents with psychotherapy, 3) screen and treat depressed residents with pharmacotherapy, 4) screen and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 50 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…2,9,10 Residents and fellows in surgical disciplines, such as otolaryngology-head and neck surgery, are particularly at risk regarding demanding, unpredictable workload, highstakes surgeries, and nights on call. 2,11 In this cohort study, we observed significant rates of depression and sleep disorders in residents and fellows, which have increased throughout the pandemic period. Regarding US studies, the prevalence of depression ranged from 5% to 28% of residents in otolaryngology-head and neck surgery, 3,12 with a 15% increase in depressive symptoms after the start of residency.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…2,9,10 Residents and fellows in surgical disciplines, such as otolaryngology-head and neck surgery, are particularly at risk regarding demanding, unpredictable workload, highstakes surgeries, and nights on call. 2,11 In this cohort study, we observed significant rates of depression and sleep disorders in residents and fellows, which have increased throughout the pandemic period. Regarding US studies, the prevalence of depression ranged from 5% to 28% of residents in otolaryngology-head and neck surgery, 3,12 with a 15% increase in depressive symptoms after the start of residency.…”
Section: Discussionmentioning
confidence: 74%
“…Pandemics may be associated with negative outcomes in the workload, stress, sleep and mental health status of health care workers . Residents and fellows in surgical disciplines, such as otolaryngology–head and neck surgery, are particularly at risk regarding demanding, unpredictable workload, high-stakes surgeries, and nights on call …”
Section: Discussionmentioning
confidence: 99%
“…Of the 25 included articles, only 1 aimed to determine cost-effectiveness of an intervention to improve well-being. 55 However, cost-effectiveness was not considered from the institutional (ie, the health system within which residents work) perspective. Specifically, the authors used incremental cost-effectiveness ratios to compare the cost of various interventions that would be incurred by the institution (ie, through paying for resident's health insurance) relative to the resident's expected clinical outcome (ie, quality-adjusted life years 58 ) of each intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 25 articles reviewed, 1 (4%) article 55 had an aim that is directly related to our research question in that it set out to determine the cost-effectiveness of screening and treating for depression (a critical detractor from well-being); however, cost-effectiveness was not considered from the institutional perspective. Aims of the other 24 (96%) articles were related to factors that impact well-being (eg, burnout, stress) or workplace sequelae of poor well-being (eg, attrition), but not economics of these elements.…”
Section: Study Aims Relative To Scoping Review Research Questionmentioning
confidence: 99%
See 1 more Smart Citation